An observational study of clinicoetiological profile of stroke patients in a new tertiary care hospital in North Odisha, India - Behera, Bibhu P.; Maharana, D. N.; Mohanty, Partha S. (International Journal of Research in Medical Sciences, 2019)
Background: Stroke is one of the leading causes of morbidity and mortality in India. The objective was to study the clinical profile, risk factors, neurological characters, pattern of brain stroke, areas of brain affected as per CT scan findings in patients with stroke. Methods: This observational study was carried out from June 2018 to Jan 2019 of all new patients admitted with stroke in Pandit Raghunath Murmu Medical College and Hospital, Baripada, Mayurbhanj, Odisha, India. Results: The incidence of stroke is maximum in 46-60 years of age group. The average age+SD was 59.3+13.5 in our study. 274 (46.52%) patients had ischemic stroke and 315 (53.48%) patients had hemorrhagic stroke. The male to female ratio was 1.46:1. Anterior circulation (86.42%) was the most common territory involved in the brain. The most common risk factor was hypertension with 77.76% followed by dyslipidemia (53.99%). The most common clinical presentation was hemiplegia (85.23%). Conclusions: The incidence of stroke is maximum in 46-60 years of age group. The average age+SD was 59.3+13.5 in our study. 274 (46.52%) patients had ischemic stroke and 315 (53.48%) patients had hemorrhagic stroke. The male to female ratio was 1.46:1. Anterior circulation (86.42%) was the most common territory involved in the brain. The most common risk factor was hypertension with 77.76% followed by dyslipidemia (53.99%). The most common clinical presentation was hemiplegia (85.23%).